Symbiotic Penalties in Islamic Criminal Legislation, Atonement as a Model: A comparative study - Ela'awar, Mohammed Shawqi Naser (Journal of Islamic Sciences, 2021)
Penalties in Islamic criminal legislation This research discusses the symbiotic a comparative doctrinal study. It addresses the definition of penalty - atonements as a model provisions in the Islamic system, and the provisions of symbiotic punishments in the atonement role in social solidarity. It also sheds light on the opinions of jurists in symbiotic and their positive punishments, and whether these expiations are punishments or types of reformation. In addition, of each particular we address in this research the types of symbiotic atonement and the type.The main goal is to examine the position of the Yemeni Sharia and legislation on symbiosis. atonement punishments This research is based on the inductive and analytical approach by extrapolating the words of Islamic scholars in the rule of atonements and their provisions. The approach depends on the analysis and discussion of what each team went to, while indicating the amounts of symbiotic punishments in the atonements such as food and clothing. The conclusion of the research sums up the most important findings of this research as well as recommendations.
Keywords: Penalties; Solidarity; Atonement; Oath; Vow; Murder; purification; Ransom; Intercourse